Removal of anionic dyes by magnetic modified A.barbadensis Miller residue leaves as a bio-adsorbent using biosorption process - Shweta Gupta; Amit Prajapati; Arinjay Kumar (Green Technologies and Sustainability)
The method of using waste from A.barbadensis miller leaves powder as a biosorbent has shown promise in treating wastewater, there has not been much research done on magnetized​ biosorbent up to this extent. This study investigates the biosorption of anionic dyes Direct blue dyes – 86 and Acid yellow-36 from aqueous solution by magnetic Modified A. barbadense Miller leaves derived (MMABL). The Synthesis of MMABL, physicochemical characteristics have been investigated by VSM, BET, XRD, SEM-EDX, FTIR. To study the effect of pH (1–9), Concentration (10–200 mg/l), Contact Time (10–60 min) Temperature (283–323 K), kinetics, isotherms and thermodynamics on the biosorption of dyes batch biosorption experiments were conducted. Optimum values of this conduct experiment at 100mg/l aqueous dye solution, 0.6 g of MMABL, pH 2, RPM 170, Temp 303 K, Time 40 min. The kinetic study demonstrated pseudo second order fitted well both the anionic dyes and Langmuir adsorption isotherm model best represented biosorption results with the maximum monolayer adsorption capacity of 75.18 mg/l for AY-36 and 312.5 mg/l for DB -86. According to the thermodynamics parameters biosorption process were spontaneous and favoured endothermic reaction. Regeneration and reusability of MMABL were investigated. The findings in this research are suggesting MMABL as an inexpensive biosorbent that demonstrates high efficacy for anionic dyes removal in a more realistic biosorption system.